Docosahexaenoic acid inhibits TNF-α-induced osteoclast formation and orthodontic tooth movement through GPR120 - Ma, Jinghan; Kitaura, Hideki; Ogawa, Saika; Ohori, Fumitoshi; Noguchi, Takahiro; Marahleh, Aseel; Nara, Yasuhiko; Pramusita, Adya; Kinjo, Ria; Kanou, Kayoko; Kishikawa, Akiko; Ichimura, Atsuhiko; et al. (Frontiers in Immunology, 2023)
Docosahexaenoic acid (DHA) is an omega-3 fatty acid, which has a number of benefits for human health, including anti-inflammatory effects and inhibition of osteoclast formation mediated via G protein-coupled receptor 120 (GPR120). Orthodontic force was proved to induce tumor necrosis factor-α (TNF-α) expression, which activates osteoclast differentiation during orthodontic tooth movement (OTM). The present study was performed to investigate the influence of DHA on TNF-α-induced osteoclast formation and OTM in vivo. We examined osteoclast formation and bone resorption within the calvaria of both wild-type (WT) and GPR120-deficient (GPR120-KO) mice injected with PBS, TNF-α, TNF-α and DHA, or DHA. DHA inhibited TNF-α-induced osteoclast formation and bone resorption in WT mice, but had no effect in GPR120-KO mice. OTM experiments were performed in both mouse strains with or without regular injection of DHA, and the effects of DHA on osteoclast formation in the alveolar bones during OTM were examined. DHA also suppressed OTM in WT but not GPR120-KO mice. These results showed that DHA suppresses TNF-α-induced osteoclast formation and bone resorption via GPR120. TNF-α plays a crucial role in OTM, and therefore DHA may inhibit TNF-α-induced osteoclast formation and bone resorption in OTM.